Long-Term Reliability and Validity of the AO Spine PROST (Patient-Reported Outcome Spine Trauma). Issue 17 (1st September 2022) - Buijs, George S.; de Gendt, Erin E.A.; Sadiqi, Said; Post, Marcel W.; Muijs, Sander P.J.; Oner, F. Cumhur
Abstract : Study Design: Cross-sectional validation study. Objective: The aim was to validate the AO Spine Patient-Reported Outcome Spine Trauma (PROST) at a minimum of 12 months posttrauma and to evaluate patient characteristics, types of spine fractures, and treatment strategies as determinants of AO Spine PROST scores. Summary of Background Data: The reliability and validity of the AO Spine PROST as a measure of health-related quality of life for more than 12 months after onset of spine trauma is unclear. Materials and Methods: Patients with a traumatic spine injury were recruited from a level-1 trauma center. They were asked to complete the AO Spine PROST, EuroQoL 5D-5L (EQ-5D-5L), and either Oswestry disability index (ODI) or neck disability index (NDI) for concurrent validity. Internal consistency was assessed by calculating the Cronbach α and item-total correlation coefficients. Test-retest reliability was evaluated using intraclass correlation coefficients. Spearman correlation tests were performed for the AO Spine PROST in correlation with the EQ-5D-5L, and either ODI or NDI. Determinants for AO Spine PROST score were analyzed using multivariate regression models. Results: A total of 175 patients participated in the cross-sectional arm and 49 in the test-retest arm of the study. Median duration of follow-up was 94.5 months. No floor or ceiling effects were seen. Internal consistency was excellent (α=0.98, item-total correlation coefficient: 0.73–0.91) as well as test-retest reliability (intraclass correlation coefficient=0.81). Satisfactory correlations were seen for the EQ-5D-5L (0.76; P <0.001), ODI (0.69; P <0.001), and NDI (0.68; P <0.001) with the AO Spine PROST. Multivariate linear regression models showed that having ≥1 comorbidities, duration of return to work within the range of 7 to 43 months and no return to work were significant independent determinants for a worse AO Spine PROST score. Conclusions: Very good long-term reliability and validity results were found for the AO Spine PROST.